2016
DOI: 10.2494/photopolymer.29.99
|View full text |Cite
|
Sign up to set email alerts
|

UV Curable Formulations for UV-C LEDs

Abstract: We investigated the formulations of acrylates which were applicable to UV-C LED lamps. The mixtures of acrylate monomers and photoinitiators were placed on silicon wafer or sandwiched between a silicon plate and a CaF 2 plate to obtain sample films. The films were irradiated by UV-C LED lamps which emit 265, 285, and 300 nm-lights. The effect of initiators, irradiation wavelength, and atmosphere on the conversion of the acryl unit was investigated using FT-IR spectroscopy. We found that the photoinitiator O-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…where 3 I and 3 A are the molar extinction coefficient of initiator and absorber (when present), respectively, and [I] and [A] are the concentration of initiator and absorber, respectively. Based on the values reported for the molar extinction coefficients in the literature 45,49 and keeping in mind that no absorber was used in this study, the D p of 3KSRD sample was found to be signicantly smaller than that of 1KTPO (i.e., 40 vs. 600 mm). It approves that SFH + had a dual-function as photosensitizer and photoabsorber in the system.…”
Section: Effect Of Pis On Resolutionmentioning
confidence: 68%
“…where 3 I and 3 A are the molar extinction coefficient of initiator and absorber (when present), respectively, and [I] and [A] are the concentration of initiator and absorber, respectively. Based on the values reported for the molar extinction coefficients in the literature 45,49 and keeping in mind that no absorber was used in this study, the D p of 3KSRD sample was found to be signicantly smaller than that of 1KTPO (i.e., 40 vs. 600 mm). It approves that SFH + had a dual-function as photosensitizer and photoabsorber in the system.…”
Section: Effect Of Pis On Resolutionmentioning
confidence: 68%
“…Figure 4 shows the effect of long wavelength for compensating the low intensity of the shortwavelength UV LED emission. Experiment (2) shows the thickness of the un-polymerized layer achieved with the 365 nm and 310 nm LEDs. Experiments (5) and 7 were performed with 365 and 310 nm irradiation, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…For UV LEDs to gain prominence, their UV curing performance must be comparable to that of the classical high-pressure or medium-pressure mercury lamps. Okamura et al presented the optimal formulation of monomers and photoinitiators for use with UV-C LEDs (265, 285, and 300 nm peaks) and pointed out that the UV-C LED is effective for addressing oxygen inhibition for UV curing of resins under air [2]. Taki et al compared the network structures formed by the high-pressure mercury lamp and 365 nm UV LED.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the group of Fouassier and Lalevèe investigated novel photoinitiators for LED projector 3D printing [14][15][16][17][18]. Moreover, Okamura et al used different types and formulations of photoinitiators to compare the performance of deep UV-LED with the typical highand medium-pressure mercury lamps and metal halide lamp [19]. They mainly focused on the sensitivity of the photoinitiator and conversion of C=C bond, and also briefly discussed the crosslinked structure of UV-cured monomers.…”
Section: Introductionmentioning
confidence: 99%